Public Policies to Promote Implement and Fundamental Rights at Work and International Economic Integration - Mattioli, Maria Cristina (Brazilian Journal of Latin American Studies, 2003)
The vulnerability of national economies to events and international policies has created dilemmas anddifficulties in managing national policies and international cooperation. At the same time that nations look for economicintegration, they speak political autonomy. The increasing economic integration among nations, seeking for theelimination of economic differences, emerges as a limitation of this national autonomy, resulting, insofar, in tension.This tension is clearly seen at the labor market, at the time of implementation and enforcement of fundamental laborrights, as internationally recognizes by the ILO Declaration of 1998. The emerging conclusion is that policies can only beimplemented through the strengthening of international organizations, such as the ILO and the WTO, stipulating thattheir member states be responsible for the implementation of those policies ar a national level. Certainly, this attitude canbe seen as a representation of national autonomy derogation in face of global movements, as a result of a harmonizedregulation depending on international enforcement, through socias clauses, included in international trade agreements.